Contextual Learning with Megapodius reinwardt Ecotourism: A Sustainable Education Approach and Its Impact on Students' Science Process Skills - Yamin, Muhammad; Jufri, A Wahab; Jamaluddin; Termizi Borhan, Mohamad; Hardianti, Bq. Sri Widia (Jurnal Pendidikan IPA Indonesia, 2025)
This study examines the potential of Megapodius reinwardt as an ecotourism attraction and learning resource, as well as the implications of ecotourism-based contextual teaching and learning (CTL) on students' science process skills. The approach employed was a mixed-methods design in both the experimental and control classes. Science process skills data were collected through observation and written pre-tests and post-tests in both groups. Data analysis was conducted both quantitatively and descriptively, as well as qualitatively. Quantitative analysis was conducted on ecological indices, resource use, and the implications of CTL on science process skill. The seven groups of experimental students identified 14-16 characteristics of M. reinwardt, including eight unique aspects: nests in the form of mounds of soil mixed with litter, built cooperatively, used collectively, repeatedly, large eggs, buried in the ground, do not incubate their eggs, and do not raise young. Four environmental factors have a big effect on how many M. reinwardt there are: how far away they are from the river channel, what kind of trash they are in, how bright the light is, and how dense the vegetation is.  The        N-gain analysis of post-test scores between the experimental and control classes, employing the Mann-Whitney Test, produced an Asymp Sig value of 0.00 ≤ 0.05, signifying a substantial enhancement in students' science process skills within the experimental class.  Ecotourism-based CTL has beneficial and substantial effects on students' scientific process skills while concurrently facilitating the achievement of the Sustainable Development Goals (SDGs) through community empowerment, economic enhancement, environmental preservation, and the advancement of sustainable education.